'Culture' as a discursive resource in newspaper articles from Le Monde about secularism: constructing 'us' through strategic oppositions with religion. Issue 3 (3rd July 2018) - Sommier, Mélodine
ABSTRACT: Building on research highlighting the complex webs of relations between secularism, culture, and religion, this study investigates how the concept of culture was utilized in discourses of laïcité from the newspaper le Monde . Articles ( N  = 76) published between 2011 and 2014 were analyzed using qualitative content analysis. Results revealed the agency associated with the use of culture as it was strategically – rather than systematically – used in opposition to religion. Overall, culture – and the practices it defined – tended to be represented as normal and invisible. On the other hand, religion tended to be constructed as a disruption to secularism and the corresponding cultural reality. The findings therefore suggested culture could be strategically used to validate and regulate specific practices as well as representations of the imagined community. This study complements previous research on discourses of secularism by drawing attention to the strategic divisions between culture and religion, and their implications. The findings draw attention to the construction of a secular imagined community because of the punctual and strategic use of culture and religion as proxies for 'us' and 'them'. Thus, the findings have practical implications as regards religious minorities' identification with and belonging to the nation.